2019
DOI: 10.1111/sdi.12774
|View full text |Cite
|
Sign up to set email alerts
|

Is surgical PD catheter insertion safe for urgent‐start peritoneal dialysis?

Abstract: Urgent‐start peritoneal dialysis (USPD) is increasingly seen as a viable alternative to hemodialysis through a central venous catheter for late‐presenting end‐stage renal disease patients. However, concerns remain about starting dialysis early following the surgical implantation of the peritoneal dialysis (PD) catheter; urgent PD is often thought to be a safe option only after minimally invasive percutaneous catheter insertions. Analysis of the cumulative data from published literature presented in this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…14 Furthermore, leaks have been reported in urgent-start PD at a rate of 0% to 7.7%, 5% to 20%, and 0% to 33% depending on the surgical approach (i.e., open, laparoscopic, and percutaneous, respectively). 15 Compared with elective-start PD, urgent-start PD had lower rates of catheter dysfunction (i.e., 17.2% vs. 28.4%) yet higher rates of catheter leakage (13.8% vs. 3.3%). 16 The high number of leaks in this study could be associated with the short catheter break-in time.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…14 Furthermore, leaks have been reported in urgent-start PD at a rate of 0% to 7.7%, 5% to 20%, and 0% to 33% depending on the surgical approach (i.e., open, laparoscopic, and percutaneous, respectively). 15 Compared with elective-start PD, urgent-start PD had lower rates of catheter dysfunction (i.e., 17.2% vs. 28.4%) yet higher rates of catheter leakage (13.8% vs. 3.3%). 16 The high number of leaks in this study could be associated with the short catheter break-in time.…”
Section: Discussionmentioning
confidence: 89%
“…Previously, catheter migration was associated with the surgical placement technique; open, laparoscopic, and percutaneous placement techniques were associated with rates of migration of 3.1% to 15.4%, 0% to 20%, and 6% to 20%, respectively. 15 Furthermore, the need for catheter repositioning was higher in patients whose catheter break-in period was less than 48 hours (i.e., 14.6% vs. 3.4%, P ¼ 0.009). 17 In patients with continuous ambulatory PD, catheter break-in periods of less than 2 weeks are feasible and safe.…”
Section: Discussionmentioning
confidence: 95%
“…Urgent initiation of PD by the surgical placement of PD catheters is considered a reasonable alternative to the urgent start of haemodialysis for unplanned dialysis, provided that respective expertise and infrastructure are available. 8 As demonstrated in our study, surgical placement of PD catheters is safe and effective for urgent PD initiation, potentiating PD utilisation as a dialysis modality of choice.…”
Section: In: Interventional Nephrologymentioning
confidence: 53%
“…However, research has shown that mechanical complications are independent of the catheter insertion technique and steps aimed at minimizing intraperitoneal pressures like low initial volume and strict supine posture in the early period are extremely essential in minimizing catheterrelated complications. 33 The high incidence of mechanical complications in the study of Dias et al 22 can therefore be explained by the high-volume PD used in their study. However, two recent metaanalyses comparing urgent-start PD with planned PD has shown that the risk of leakage and other mechanical complications are significantly higher with urgent-start PD.…”
Section: Discussionmentioning
confidence: 88%